2012
DOI: 10.1103/physrevb.85.195402
|View full text |Cite
|
Sign up to set email alerts
|

Spin and orbital angular momentum structure of Cu(111) and Au(111) surface states

Abstract: We performed angle resolved photoemission (ARPES) studies on Cu(111) and Au(111) surface states with circularly polarized light. Existence of local orbital angular momentum (OAM) is confirmed as has been predicted to be broadly present in a system with an inversion symmetry breaking (ISB). The single band of Cu(111) surface states is found to have chiral OAM in spite of very small spin-orbit coupling (SOC) in Cu, which is consistent with theoretical prediction. As for Au(111), we observe split bands for which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
110
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 26 publications
12
110
2
1
Order By: Relevance
“…(4). Such quasi-linear OAM patterns for the upper two bands of STO surface states is a strong, testable prediction that can be confirmed readily by the recently popular technique of circular dichroism ARPES [11,12,19].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…(4). Such quasi-linear OAM patterns for the upper two bands of STO surface states is a strong, testable prediction that can be confirmed readily by the recently popular technique of circular dichroism ARPES [11,12,19].…”
mentioning
confidence: 82%
“…The chiral structure of OAM, on the other hand, should be readily observable by means of circular dichroism ARPES [12,19]. The two would-be Rashba-split bands possess the same orbital chirality in STO, and therefore give rise to the same circular dichroism response.…”
mentioning
confidence: 99%
“…After the new model was proposed, it was also found experimentally and theoretically that chiral OAM structure exists in surface states of metals [19][20][21][22] even when SOC is weak. Somewhat surprisingly, it was found that the alignment(parallel or anti-parallel) between spin and OAM are band and crystal momentum dependent.…”
mentioning
confidence: 99%
“…However, there is no general * alberto.crepaldi@elettra.eu consensus about the physical mechanism at the origin of the dichroism in CD-ARPES experiments. Recent theoretical and experimental studies proposed to interpret the dichroism in giant spin-split states in surface alloys [17][18][19] and in TIs [20][21][22][23] as the result of local orbital angular momentum (OAM [17,18,21,(24)(25)(26)) or directly as a measure of the spin polarization [20].Recently, a large variation of the dichroism as a function of the incoming photon energy as well as the change in its sign have been reported by Scholz and co-workers for the topological insulator Bi 2 Te 3 [27]. A similar observation was reported for the TI Bi 2 Te 2 Se by Neupane et al [28].…”
mentioning
confidence: 99%